Emotional and behavioural reactions to melanoma genomic risk information. (1st June 2019) - Fenton, G.L.; Smit, A.K.; Keogh, L.; Cust, A.E.
Summary: Melanoma is the most deadly type of skin cancer, and in countries like Australia, the number of people who develop melanoma is high. A new approach to further improving the prevention and early detection of melanoma aims to better understand people's chances, or risk, of developing melanoma by looking at their genes and then providing them with their genetic risk of melanoma information. This Australian‐based study explored how people react to receiving this type of information. Thirty people were interviewed who had no personal history of melanoma and had previously received their genetic risk results, along with information on how to prevent melanoma and a telephone call from a genetic counsellor. Several considerations influenced how participants felt and behaved in response to their risk results, including their expectations for their genetic risk, their thoughts on their melanoma risk before testing and how they already protected themselves from the sun. There were many positive reactions and a number of participants said it had changed their behaviour in the sun for the better by increasing their knowledge and awareness of melanoma. While some participants described having negative emotions such as disappointment and worry, these improved with time. The results from this study improves our understanding of emotional and behavioural responses to melanoma genetic risk information and will assist in developing educational and support resources for people who have genetic testing.